The Relationship Among Intra-Amniotic Inflammatory Response, The Progression of Inflammation in Chorionic Plate and Early-Onset Neonatal Sepsis - Moon, Kyung Chul; Oh, Jeong-Won; Park, Chan-Wook; Park, Joong Shin; Jun, Jong Kwan (Frontiers in Pediatrics, 2021)
Background:Chorionic-plate(CP) has been denigrated by the well-known route of extra-placental membranes from decidua-parietalis through chorion to amnion in the progression of ascending intra-uterine infection among preterm-births(PTBs). However, considering previous-studies reporting the relationship among intra-amniotic inflammatory-response(IAIR), the progression of inflammation in extra-placental membranes and early-onset neonatal sepsis(EONS), and the anatomic-connection between extra-placental membranes and CP, there is a good-chance that IAIR would be more-likely and severe according-to the progression of inflammation in CP and this-progression of inflammation in CP would be associated with a significant-increase of EONS in neonates delivered due-to either PTL or preterm-PROM. Unfortunately, there is no-information about the relationship among IAIR, the progression of inflammation in CP and EONS among spontaneous-PTBs. The objective of current-study is to examine this-issue. Method:Study-population included 309singleton pregnant-women delivered preterm-neonates with the following-conditions:1)gestational-age(GA) at delivery:20.0~36.9weeks;2)spontaneous-PTBs:PTL(151cases) or preterm-PROM(158 cases);3)available-results of placental histologic-examination;4)without congenital-anomaly;and5)delivery within 60hours of amniocentesis. We examined IAIR, and the frequency of intra-amniotic inflammation(IAI) and EONS according-to the progression of inflammation in CP(i.e., stage-0,inflammation-free CP;stage-1,inflammation restricted to subchorionic-fibrin[SCF];stage-2,inflammation in connective-tissue[CT] of CP but without chorionic-vasculitis;stage-3,chorionic-vasculitis). IAIR was determined by amniotic-fluid(AF) matrix metalloproteinase-8(MMP-8) concentration(ng/ml) and IAI was defined-as an elevated AF MMP-8 concentration(≥23ng/ml). EONS included either suspected or proven-EONS. Results:1)Each stage (stage-0~stage-3) was present in 69.3%(214/309), 15.9%(49/309), 11.0%(34/309), 3.9%(12/309) of study-population respectively;2)AF MMP-8 concentrations continuously elevated according-to the progression of inflammation in CP(stage-0vs.stage-1vs.stage-2vs.stage-3;median[ng/ml],range[ng/ml]; 6.0[0.3-4202.7]vs.153.9[0.3-6142.6]vs.464.9[5.8-3929.0]vs.1780.4[35.1-5019.5];Kruskal-Wallis-test, P<0.001 and Spearman's rank-correlation-test, P<0.000001,r=0.553);3)Moreover, the frequency of IAI and EONS gradually-increased with the progression of inflammation in CP(stage-0vs.stage-1vs.stage-2vs.stage-3;IAI, 30.5%[64/210]vs.70.2%[33/47]vs.96.7%[29/30]vs.100%[12/12];EONS, 3.5%[7/200]vs.25.5%[12/47]vs.32.3%[10/31]vs.40.0%[4/10];each for Pearson's chi-square-test, P<0.000001 and linear-by-linear-association,P<0.000001);4)Of-note, multiple-logistic-regression-analysis demonstrated that a more advanced-stage in the progression of inflammation within CP was associated with a higher odds-ratio(OR) for EONS(stage-1vs.stage-2vs.stage-3;OR, 7.215, 95%confidence-interval[CI][2.177-23.908]vs.OR, 10.705, 95%CI[2.613-43.849]vs.OR, 27.189, 95%CI[2.557-289.124]) as compared with stage-0 even after the adjustment for potential confounding-variables. Conclusion:IAIR is more-likely and severe according-to the progression of inflammation in CP, and this-progression of inflammation in CP is an independent risk-factor for EONS in spontaneous-PTBs. This-finding suggests that CP may be another-playground for the progression of ascending intra-uterine infection in addition to extra-placental membranes, and the progression of inflammation in CP may be used for the prediction of EONS in spontaneous-PTBs.